RESILIENSI PADA LANSIA - Andria Pragholapati; Fitri Munawaroh (LPPM STIKES Muhammadiyah Kendal, 2020)
Psychologically, the elderly (elderly) is a phase of development that demands to be able to adjust to changes that occur physically and psychologically. Depression is a disease that often occurs among the elderly. To deal with stress, depression, and anxiety requires a resilient attitude. Every individual has the ability to be resilient naturally, but this must be nurtured and honed. This study aims to determine the picture of resilience in the elderly at the Social Protection Center in Tresna Wredha Ciparay. This research uses quantitative descriptive method. The population in this study is the elderly at the Panti Wredha as many as 150 people. The number of samples in this study were 60 with slovin sampling techniques. Data collection using a questionnaire. The analysis used is univariate analysis. The results showed that the majority of elderly people at the Tresna Wredha Ciparay Social Protection Center had a high level of resilience.